Hydrophobic recognition allows the glycosyltransferase UGT76G1 to catalyze its substrate in two orientations - Ting Yang (Nature Portfolio, 2019)
UGT76G1 is an UDP-glucose dependent glycosyltransferase and a component of the biosynthesis pathway for the natural sugar substitute steviol glycoside. Here, the authors present substrate bound crystal structures of UGT76G1 and provide insights into substrate recognition and catalysis by the enzyme.